Development of core entrustable professional activities for Indonesian undergraduate medical education: the experience of Universitas Muhammadiyah Jakarta - Oktarina,; Mohd Nasri AB,; Tirta PS,; Alidina NA, (Penerbit UKM, 2023)
Indonesia has implemented Competency-Based Education (CBE) since 2006 based on a national standard for physician competencies. This study aimed to develop Core Entrustable Professional Activities (EPAs) for Indonesian undergraduate medical programs to remedy the challenge of translating competencies into professional activities in CBE. Two rounds of modified Delphi were employed in October November 2022. The research subjects selected were (i) experts in medicine such as internal medicine, surgery, medical education, etc., and (ii) medical teachers in the preclinical/clinical stage for two years or more. Fifteen experts were involved in both Delphi rounds. The first Delphi instrument referring to literature frameworks included 34 professional activities for individual healthcare tasks and 17 for family community medicine/public health. The second Delphi instruments used were based on the first-round results. After the first Delphi, 31 individual healthcare tasks and all family-community medicine/public health tasks reached a consensus. One expert suggested two additional family-community medicine/public health activities. The second Delphi instrument listed the percentage of agreement for individual healthcare tasks and family-community medicine/public health tasks, including the two additional activities. After the second-round of Delphi, two individual healthcare tasks and one family-community medicine/public health task had not reached a consensus However, 94.7% of activities were still acceptable as Core EPAs in family-community medicine and public health services. In conclusion, developing EPAs for undergraduate medical programs using two rounds of the Delphi method resulted in 32 individual medical service activities and 18 family medicine-community/public health tasks. These core EPAs were expected to facilitate the translation of competencies into professional activities.